Vertical ventilation concepts for future passenger cars. (1st February 2018) - Dehne, Tobias; Lange, Pascal; Volkmann, André; Schmeling, Daniel; Konstantinov, Mikhail; Bosbach, Johannes
Abstract: We compared three vertical ventilation concepts to dashboard ventilation in a generic car cabin with the aim to improve thermal passenger comfort and energy efficiency of future cars. Temperatures were analyzed with an infrared camera and local temperature sensors. Omnidirectional velocity probes were used to capture the fluid velocities and temperatures in the vicinity of thermal passenger dummies, which were used to simulate the thermal impact of the passengers. Further, the ventilation efficiency was measured with the tracer gas technique using humidity sensors in the vicinity of the dummies and in the air outlets. Besides the experimental investigations, the relevant flow cases were studied by Computational Fluid Dynamics simulations using the RANS method, providing insight into the complex and three-dimensional flow structures of the passenger compartment. Validation of the simulations with the experimental data revealed acceptable consistency, however, with local deviations indicating further need for experimental investigations. The ventilation efficiencies of the vertical ventilation concepts were at least comparable or even better as compared to dashboard ventilation. Regarding the comfort-relevant flow parameters, dashboard ventilation stood out with the lowest temperature stratification but revealed comfort-critical flow velocities. The vertical ventilation concepts allowed for comfortable velocities, but tended to produce comfort-critical temperature stratifications. Pursuing the equivalent temperatures, the vertical systems revealed an improved heating performance over dashboard ventilation. During summer and spring/fall conditions, low momentum ceiling ventilation as well as the combination of cabin displacement ventilation and low momentum ceiling ventilation were able to provide comfortable equivalent temperature distributions. Highlights: Low-momentum ventilation revealed significant advantages over dashboard ventilation. Heating efficiency was drastically improved in winter case. Thermal comfort in spring/fall and summer cases was superior to dashboard ventilation. Ventilation efficiencies were comparable or even better than dashboard ventilation.